Micropatterned Poly(D,L-Lactide-Co-Caprolactone) Conduits With KHI-Peptide and NGF Promote Peripheral Nerve Repair After Severe Traction Injury - Yu, Xing; Zhang, Deteng; Liu, Chang; Liu, Zhaodi; Li, Yujun; Zhao, Qunzi; Gao, Changyou; Wang, Yong (Frontiers in Bioengineering and Biotechnology, 2021)
Severe traction injuries after stretch to peripheral nerves are common and challenging to repair. The nerve guidance conduits (NGCs) are promising in the regeneration and functional recovery after nerve injuries. To enhance the repair of severe nerve traction injuries, in this study KHIFSDDSSE (KHI) peptides were grafted on a porous and micropatterned poly(D, L-lactide-co-caprolactone) (PLCL) film (MPLCL), which was further loaded with nerve growth factor (NGF). The adhesion number of Schwann sells (SCs), ratio of length/width (L/W), and percentage of elongated SCs were significantly higher in the MPLCL-Peptides group and MPLCL-Peptides-NGF group compared with those in the PLCL group in vitro. The electromyography (EMG) and morphological changes of nerve after severe traction injury were improved significantly in the MPLCL-Peptides group and MPLCL-Peptides-NGF group compared with those in the PLCL group in vivo. Hence, the NGCs featured with both bioactive factors (KHI peptides and NGF) and physical topography (parallelly linear micropatterns) have synergistic effect on nerve reinnervation after severe traction injuries.